Eco-marine reading literacy: a conceptual framework for environmentally contextualized multimodal literacy in global EFL education - Nyak Mutia Ismail (Erudita: Journal of English Language Teaching, 2026)
The present study proposes a conceptual framework to add environmental awareness to EFL reading literacy in terms of Eco-Marine Reading Literacy. The concepts involved are reading literacy, eco-literacy, place-based education, culturally sustaining pedagogy, the Cognitive Theory of Multimedia Learning, and multimodality theory. Instead of collecting data through direct observation, the research operates from definition to construct an entire model on theory alone that links cognitive reading, ecological content alignment, contextual-cultural basis and multimodal representation. This analysis shows that these theoretical approaches are not at odds but speak to different structural aspects of literacy. Reading literacy explains cognitive processes of comprehension, eco-literacy content oriented toward sustainability, contextual pedagogies orient learning toward local cultural realities, and multimedia theories describe how meaning is mediated in digital environments. The proposed EMRL framework combines these dimensions into a single lens through which literacy is understood as both a cognitive and socio-ecological practice. The framework offers a theoretical foundation for bridging gaps between language education; and it is flexible as well as susceptible to adaptation across ranges of education. This study fills a part of the gap in EFL literacy by adopting an ecologically situated learning to interpret digitally enhanced 21st century literacy.